In silico sequence analysis, homology modeling and function annotation of putative subtilisin-like serine protease from Cryptosporidium parvum - Mat Yusof, Afzan; Md Isa, Muhammad Lokman (2018)
Purpose: This study predicted three-dimensional (3D) protein structure of Cryptosporidium parvum subtilisin-like serine protease (CpSUB) using homology modelling as the approach of 3D structure prediction. Methods: CpSUB is an extracellular protein comprising of 1324 amino acid residues. Its amino acid sequence was computed to determine the physiochemical properties. 3D protein structure was developed by using MODELLER v9.18 software before subjected to model refinement and assessment. The refined model was then computed for functional annotation. Quality assessment analysis of the protein model for CpSUB through its PROCHECK Ramachandran Plot and other reliable protein structure assessment tools indicated that the selected protein model is a reliable model. Result: The result from functional annotation revealed that it is sorted to cd07473 superfamily or peptidase S8 family domain in subtilisin-like proteins. To our best knowledge, this protein model of CpSUB was first proposed for the modeling of 3D structure despite not having a crystallized protein structure deposited yet in Protein Data Bank (PDB). Conclusion: Thus, this study may provide understanding to the molecular and structural function of CpSUB. This predicted 3D model may be further studied for wet lab characterization studies and may be used for a prospective therapeutic anti-cryptosporidial agent.